Factors Affecting Adoption of Climate-resilient Indigenous Agricultural Technologies and Practices: A Case Study from Nepal - Bhatt, Sandeep; Bhatta, Kiran Prasad (Far Western Review, 2025)
Climate change has been one of the detrimental factors affecting agriculture production. Climate resilient indigenous agricultural technologies and practices tend to be effective in combating the ill-effect of changing climate and associated vulnerabilities. Hence, this research endeavors to find out the adoption of such indigenous technologies and practices and its impact on farming. A survey was conducted in the 66 farmers of Jagannatha village of Dasharathchanda Municipality, Baitadi. A pre-tested semi structured questionnaire was used to collect the data. The findings revealed that indigenous technologies and practices like nutrient management and plant protection methods were adopted by higher proportion of the farmers compared to other such technologies and practices from sowing to harvest. The logit regression analysis for the adoption of climate resilient indigenous agricultural technologies and practices revealed that commercialized farms and farmers receiving external support like subsidies had lower chances of adoption of climate resilient indigenous agricultural technologies and practices. Lack of awareness about climate change was the major problem for adoption of climate resilient practices. Farmers never felt its need to overcome the challenges posed by climate change. From the study, it could be concluded that creating the awareness about climate change, climate resilient indigenous agricultural technologies, and formal education of the household head play an important role in understanding the value of indigenous agricultural technologies and practices. Similarly, female household heads were more likely to adopt indigenous agricultural technologies and practices suggesting for the consideration in development interventions.